A new species of Haploglenius Burmeister, 1839 (Neuroptera: Ascalaphidae) from the Colombian Orinoquía - Camacho, Adrian Ardila; Jones, Joshua R. (Zootaxa, 2012)
A new species of Haploglenius Burmeister, 1839 from Colombia (H. abdominevittatus Ardila & Jones sp. nov.) is described.This species is unique among members of Haploglenius—which are newly diagnosed here under a slightly revised definitionby the presence of three rows of anal cells in the hind wing—in having both a well-developed axillary angle and a highly exca-vated posterior margin at the base of the forewing, characters normally distinctive of other Neotropical genera of Haploglenii-nae. This species also exhibits unique color patterning on the abdomen. The male genitalia are illustrated, a first for species in the genus.